Public vs Private Space of Parking: Zoning, Accessibility, and Etalage - Triyatni Martosenjoyo (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2020)
Public parking spaces are facilities that support the activities of urban residents with relatively high mobility. As with all definitions of public spaces, public parking space facilities are assumed to be accessible to everyone without questioning their status. Several different things are found in public parking spaces in higher education institutions at UNHAS. This research examines the meaning of public parking spaces for UNHAS people and how they are connected to these facilities. The study was conducted at the Tamalanrea UNHAS campus. Data were collected using in-depth interviews to explore how they perceive zoning meanings, accessibility of public parking spaces, the signages placed there, and observations surrounding campus parking spaces. The interview involved 140 informants consisting of structural officials, lecturers, employees, students, and guests. The results showed that, in practice, the public parking space of UNHAS had become a private space because it cannot be accessed and used freely by everyone, except those with specific social status as written on parking signs (i.e., rector, vice-rector). It is also found that parking spaces have become an etalage for displaying and promoting the personal social status of UNHAS officials.